2023
DOI: 10.3390/su15043489
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Impact of Industrial Structure Upgrading and Energy Structure Optimization on Carbon Emission Reduction

Abstract: In China, there has been a significant increase in carbon emissions in the new era. Therefore, evaluating the influence of industrial structure upgrades and energy structure optimization on reducing carbon emissions is the objective of this research. Based on the provincial panel data of 30 provinces and cities across China from 1997 to 2019, this paper builds up a fixed-effect panel quantile STIRPAT model to investigate the differences in the impact of industrial structure on carbon emission intensity at diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Fourthly, energy efficiency (EE) is depicted by the economic benefit per unit of energy [33]. Lastly, electricity structure (ES) is characterized by the proportion of thermal power generation [34].…”
Section: Variable Selection and Datamentioning
confidence: 99%
“…Fourthly, energy efficiency (EE) is depicted by the economic benefit per unit of energy [33]. Lastly, electricity structure (ES) is characterized by the proportion of thermal power generation [34].…”
Section: Variable Selection and Datamentioning
confidence: 99%
“…In addition, it can also be found that the development of commercial economy and the improvement of human capital have an obvious effect on the upgrading of industrial structure, and improving the level of science and education is more beneficial to the low carbonization of industrial internal structure [32].…”
Section: The Threshold Regression Analysismentioning
confidence: 99%
“…With the improvement in innovation level, technological changes are brought about, and new technologies can effectively drive traditional industrial upgrading through penetration, overturn, and reconstruction, which is attributed to their high added values, high correlation, and high permeability [67]. With the continuous advances in industrial structure, the pollution problems caused by traditional industrial structures will gradually be relieved and, finally, the green sustainable development of cities will be realized [68].…”
Section: Industrial Structure Optimization Effectmentioning
confidence: 99%